If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 2) = 49 Reorder the terms: -10(2 + s) = 49 (2 * -10 + s * -10) = 49 (-20 + -10s) = 49 Solving -20 + -10s = 49 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -10s = 49 + 20 Combine like terms: -20 + 20 = 0 0 + -10s = 49 + 20 -10s = 49 + 20 Combine like terms: 49 + 20 = 69 -10s = 69 Divide each side by '-10'. s = -6.9 Simplifying s = -6.9
| ln(y-a)=lnb+0.5lnx | | 6+0.33333333y=10+12x | | sen^4x-2senx+1=o | | 25m^2-125m^3-81n^2+729n^3= | | 5(4x-5)-3(x+1)-19x= | | 30+1x+6=26+7x | | sen^2x=2cosx+2 | | 1,3,7,15,31= | | 16y-2=19y+16 | | q^2+11q+18=0 | | 12y+15x=141 | | x^2-6x+9=4x | | 25x-6=45x+2 | | f(x)=2.2(5)x | | T-65=75 | | x=-7+4(1.5) | | 8y-3=10+5 | | -3(5a-4)=132 | | x=-7+4y(1.5) | | 8m-5n=5m+7 | | 6x+20=4x+13 | | log(y)=9t-4 | | 76=x^3+3*x | | 8x+2=7(x-2)+4 | | 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v |